Analysis of Factors Influencing the Level of Welfare of the Community of Balikpapan City - Asih Mulyani; Aji Sofyan Effendi; Muhammad Awaluddin (International Journal of Economics, Commerce, and Management, 2024)
The purpose of this study is to determine the influence of factors that affect the level of public welfare in Balikpapan City in the period 2006-2023. The method used in the study is the quantitative data analysis method and the data analysis method using a path diagram with 4 dimensions of measurement, namely, the Level of Public Welfare measured by the Human Development Index (HDI), the Income Inequality Index measured by the Gini Ratio Index, Economic Growth, Population Growth Rate. The results of this study indicate that Economic Growth has a negative but insignificant effect on Income Disparity (Gini Ratio Index), Population Growth has a negative and significant effect on Income Disparity (Gini Ratio Index), Economic Growth directly has a positive but insignificant effect on the level of population welfare (Human Development Index), Population Growth directly has a negative but insignificant effect on the level of population welfare (Human Development Index), Income Disparity Level (Gini Ratio) has a positive and significant effect on the Level of Community Welfare (HDI) of Balikpapan City, Economic Growth through the Formation of Population Welfare (Gini Ratio Index) has a negative effect on the Level of Community Welfare (HDI) of Balikpapan City and Population Growth through the Formation of Population Welfare (Gini Ratio Index) has a negative effect on the Level of Community Welfare (HDI) of Balikpapan City.